PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELLING UNTUK MENINGKATKAN PEMAHAMAN PERENCANAAN KARIR SISWA KELAS XII.11 SMA NEGERI 1 DENPASAR TAHUN AJARAN 2024 - Dwi Umi Badriyah; Agung Nugraha Adhiputra; Dimas Heru Sumadi; M. Zainul Majdi (Journal Prakarsa Paedagogia, 2024)
This research is motivated by the fact that some students have a low understanding of career planning. Career issues are future challenges that students face. The high school years are crucial for determining a better career path. Students need to be equipped with relevant career information to make informed decisions. Therefore, this research is titled The Effect of Group Counseling Services with the Modelling Technique to Improve Career Planning Understanding in Students of Class XII.11 at SMA Negeri 1 Denpasar for the 2024/2025 Academic Year. The purpose of this study is to enhance students' understanding of career planning by using the modelling technique for students in class XII.11 at SMA Negeri 1 Denpasar. This study uses a quantitative research approach with a quasi-experimental design and a One Group Pre-test and Post-test Design. The population in this study consists of students from class XII.11, with a sample size of 6 students. Data collection techniques involved interviews and questionnaires. Based on data analysis using a t-test, the result shows that the calculated t-value is greater than the t-table value (8.145 > 2.571) at a 5% significance level, indicating that there is an effect of group counseling services with the modelling technique in improving career planning understanding for students in class XII.11 at SMA Negeri 1 Denpasar.